Caregiver-Care Recipient Relationship Closeness is Associated with Neuropsychiatric Symptoms in Dementia - Vernon, Elizabeth K. (Am J Geriatr Psychiatry, 2018)
OBJECTIVE: Closer caregiver-care recipient (CG-CR) relationships are associated with better cognitive and functional abilities, activities of daily living (in persons with dementia), and lower informal care costs. METHODS: Due to the difficulty in treating neuropsychiatric symptoms (NPSs) and their detrimental effects on caregivers and care recipients, we examined whether closeness of CG-CR relationships was associated with overall NPS severity or with specific NPS symptom domains in care recipients. In a longitudinal population-based study in Cache County, Utah, the 12-item Neuropsychiatric Inventory (NPI-12) was assessed in 300 CG-CR dyads. Caregivers reported current relationship closeness using the Whitlatch Relationship Closeness Scale. Linear mixed models examined associations between CG-CR closeness and NPI-12 total score or selected symptom domains over time (observation period: 2002–2012). RESULTS: In unadjusted linear mixed models, higher closeness scores were associated with a five-point lower NPI-12 score and a one-point lesser increase in NPI-12 per year. NPI scores also showed lower affective cluster scores (two points) and lesser increase in psychosis cluster (approximately 0.5 points per year) and agitation/aggression (0.16 points per year) for each unit increase in closeness. When controlling for NPI caregiver distress, associations between closeness and NPSs diminished to a 0.5-point lesser increase in total NPI-12 score per year. Adjusted models for NPI domains/clusters showed −0.32 points per year for the psychosis cluster, −0.11 points per year for agitation/aggression, and −0.67 overall for the affective cluster. CONCLUSION: Higher CG-CR closeness, a potentially modifiable factor, is associated with lower NPS severity and may provide a target for intervention.